Amplatzer Vascular Plug in Renal Artery Embolization: Case Serial and Review of the Literature - Billy Karundeng; Richard Sumangkut; Yuansun Khosama; Djonny E. Tjandra; Michael D. Winarto (Universitas Sam Ratulangi, 2024)
Abstract: Embolization constitutes a safe and effective therapeutic possibility in the treatment of numerous renal pathologies whether election or urgency. The use of Amplatzer vascular plug (AVP) constitutes a more recent and less widespread therapeutic choice, and its use in the renal district is not yet widespread although potentially very valid. Perioperative renal artery embolization has been introduced to reduce the risk of oncological spread and intraoperative bleeding, in order to facilitate surgery, thus decreasing perioperative morbidity. Nevertheless, in recent literature the real usefulness of perioperative renal artery embolization is still debated. Some authors agree that the advantages of perioperative renal artery embolization are to decrease intraoperative bleeding with a lower transfusion rate and to reduce operative time. Therefore, we presented five cases of renal arterial embolizations (RAEs) performed with AVP from July to August 2022 at Prof. Dr. R. D. Kandou Hospital, Manado. In all cases, a single plug was used which perfectly adapted to the target artery resulting in complete occlusion of the vessel within a short period of time. Renal artery embolization was generally performed the day before surgery under local anesthesia. After confirmation of the tumor vascularization with a contrast study, the selective renal artery embolization was performed. In our experience, the use of AVP for the treatment of renal arteriovenous fistula and neoplastic masses had given excellent results without any complications during and after the treatment. In conclusion, RAE performed with AVP has growing potential and numerous advantages in terms of the time of the procedure, speed of embolization, and precision of occlusion, but with a relative increase in costs. Keywords: amplatzer vascular plugs; vascular surgery; endovascular surgery; renal artery embolization